2020
DOI: 10.1360/ssc-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of one-dimensional nanomaterials derived from titanium carbide

Abstract: Science Bulletin 60, 71 (2015); Optical properties of one-dimensional nanomaterials based on small organic molecules SCIENTIA SINICA Chimica 41, 1240 (2011); Synthesis and transformation of one-dimensional organic-inorganic hybrid nanomaterials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Recently, Gao et al have reported Ti 3 C 2 T x MXene as a metal-free counter electrode for lead-based MAPbI 3 perovskite solar cells with PCE of 13.83%, which is ∼27.2% higher as compared to the device using the carbon electrode . Similarly, implementation of Ti 3 C 2 T x as compared to ITO as electrode in a semitransparent flexible photovoltaic (PV) device leads to the significant improvement of PCE by 13.6%, whereas in an n + –n–p + Si solar cell it has been reported that the use of Ti 3 C 2 T x as the back electrode improves the PCE up to 11% . Simultaneously, the use of Ti 3 C 2 T x as a novel ETL layer along with Au bus-bar for MAPbI 3 -based PSCs has been reported to have an efficiency of 17.17% .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gao et al have reported Ti 3 C 2 T x MXene as a metal-free counter electrode for lead-based MAPbI 3 perovskite solar cells with PCE of 13.83%, which is ∼27.2% higher as compared to the device using the carbon electrode . Similarly, implementation of Ti 3 C 2 T x as compared to ITO as electrode in a semitransparent flexible photovoltaic (PV) device leads to the significant improvement of PCE by 13.6%, whereas in an n + –n–p + Si solar cell it has been reported that the use of Ti 3 C 2 T x as the back electrode improves the PCE up to 11% . Simultaneously, the use of Ti 3 C 2 T x as a novel ETL layer along with Au bus-bar for MAPbI 3 -based PSCs has been reported to have an efficiency of 17.17% .…”
Section: Introductionmentioning
confidence: 99%